2011
DOI: 10.1155/2011/101242
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Resistance to Dietary Cholesterol

Abstract: Background. Alterations in expression of hepatic genes that could contribute to resistance to dietary cholesterol were investigated in Sprague-Dawley rats, which are known to be resistant to the serum cholesterol raising action of dietary cholesterol. Methods. Microarray analysis was used to provide a comprehensive analysis of changes in hepatic gene expression in rats in response to dietary cholesterol. Changes were confirmed by RT-PCR analysis. Western blotting was employed to measure changes in hepatic chol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 41 publications
(56 reference statements)
3
11
1
Order By: Relevance
“…Results from other studies show a lower activity of HMG-CoA reductase and lower expression of LDL receptors in the liver from rats fed a high fat diet [27]. Our study showed a significant decrease of cholesterol and triacylglycerol levels in the liver of animals treated with ATV and CoQ 10 , compared with those rats that only received ATV.…”
Section: Discussionsupporting
confidence: 66%
“…Results from other studies show a lower activity of HMG-CoA reductase and lower expression of LDL receptors in the liver from rats fed a high fat diet [27]. Our study showed a significant decrease of cholesterol and triacylglycerol levels in the liver of animals treated with ATV and CoQ 10 , compared with those rats that only received ATV.…”
Section: Discussionsupporting
confidence: 66%
“…Conversely, Spady and Cuthbert (1992) observed that rats on fed high levels of dietary cholesterol, did not exhibit suppressed hepatic LDLr activity despite a 350-fold increase in hepatic cholesterol ester levels (Spady and Cuthbert, 1992). More recently, Boone et al (2011) found that LDLr expression in Sprague-Dawley rats was not altered by dietary cholesterol. There was also a significant increase in mean hepatic cholesterol and paradoxically a decrease in serum cholesterol (Boone et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Boone et al (2011) found that LDLr expression in Sprague-Dawley rats was not altered by dietary cholesterol. There was also a significant increase in mean hepatic cholesterol and paradoxically a decrease in serum cholesterol (Boone et al, 2011). However, other studies in humans, such as Lichtenstein et al (1993) demonstrate that the addition of dietary cholesterol (~1.5 eggs per/day) to a corn oil-diet, can result in a significant increase in concentrations of total cholesterol (6%), LDL-C (8%), and HDL-C (7%), when compared to diets with low dietary cholesterol, in 14 middle-aged and older individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Boone et al. [] also reported that western blotting analysis showed dietary cholesterol significantly increases CYP7A1 protein levels in rats but not in mice. Other reports [] showed that dietary cholesterol may act to increase or decrease CYP7A1 mRNA levels in C57BL/6J mice depending on the type of fat added to the diet, and olive oil supplement caused increased expression of CYP7A1.…”
Section: The Effect Of Taurine On Cholesterol Catabolism or Bile Acidmentioning
confidence: 99%